Analysis of Prices in Squeeze-outs and Calls Preceding Them on Warsaw Stock Exchange - Królik-Kołtunik, Katarzyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The functioning of the stock market, as a regulated market, is normed in the law. In most cases, these provisions are intended to protect the non-professional market participants, individual investors or minority shareholders. An example of such legislation is to set a minimum price at which it is carried out a squeeze-out. This provision is intended to ensure minority shareholders the appropriate price in return for the repurchased shares under conditions where their position has become essentially marginal. The aim of this paper is to analyze the prices in squeeze-outs on the Warsaw Stock Exchange and in the calls preceding the squeeze-out.